New way to be a chair via distributed shared model - Dennis Anderson (Academic Chairpersons Conference Proceedings, 2023)
Being a chair in today's higher education is more stressful due to various issues related to enrollment, administration demands, and limited and shrinking resources. Chairs have to manage and juggle demands from all stakeholders including students, faculty, staff, and administration. This presentation is about how to meet these challenges by creating a shared management system that enables and empowers faculty in the department by giving them portfolios. This model moves away from chair centric model that one person holds all decision making power by controlling resources. Since my department moved to shared distributed chair model, the department productivity is higher than ever. This presentation will share this journey and how one can make such a model work.
Keywords: Chair; leadership; management; shared governance; distributed management